Application of Sanctions Against State Administrative Officials Failing to Implement Administrative Court Decisions - Hendry Julian Noor; Kardiansyah Afkar; Henning Glaser (BESTUUR, 2021)
In its constitution, Indonesia declares itself a state of law. However, government practice frequently ignores the State Administrative Court's judgements, despite the fact that court decisions are a crucial part of the state of law notion. The purpose of this research is to determine the nature, types, and execution of administrative court decisions, as well as the position of the Prosecutor's office in the Indonesian legal system. This research also examines the legal consequences for officials that do not comply with administrative court decisions. This is prescriptive and descriptive normative legal research, comprising a statute and case approach, with data collected from primary and secondary legal materials. The result of this study shows, Firstly, the results showed that the nature of administrative court decisions is erga omnes. Secondly, the position of the Prosecutor is categorized into executive power. Thirdly, state administrative officials are obliged to implement administrative court decisions. To not implementing the administrative court decision is a violation of the principle of legality. Legal consequences for government officials that do not subject to and are disobedient to the administrative court decision with legal force should still be imposed administrative sanctions by their superiors.